Biology and morphology of immature stages of Lixus canescens (Coleoptera: Curculionidae: Lixinae) - Skuhrovec, Jiří; Volovnik, Semyon (Zootaxa, 2015)
Mature larvae and pupae of Lixus (Eulixus) canescens Steven, 1829 (Curculionidae: Lixinae: Lixini) are described and compared with known larvae and pupae of other Lixus species. The biology of the species was studied in Ukraine. A species of Crambe (Brassicaceae) was identified as host plant of both larvae and adults of this weevil. The weevil is very likely oligophagous. Lixus canescens prefers dry, sunny places, such as open areas of sand close to sea shores with growing host plants. Overwintering beetles emerge in the late spring (mid-May), and then feed and mate on the host plants. The highest level of activity of the adults was observed at the end of May. Larvae are endophagous in the host plant stem. At the end of July, the larvae pupate within the stem inside a pupation cell. Adults leave the cells at the end of summer and do not hibernate on the host plants. They then, most likely, spend some time feeding on the host plants and looking for suitable shelter in which to overwinter.